Prosedur Pelayanan Penyaluran Kredit Pada PT. Bank Perekonomian Rakyat (PT.BPR VII KOTO) - Afni amanda putri (CV. ITTC INDONESIA, 2025)
This study aims to determine the credit disbursement service procedures and the obstacles encountered at PT. Bank Perekonomian Rakyat (BPR) VII Koto. The research method used interviews, literature review, and documentation with qualitative descriptive analysis. The results indicate that the credit disbursement procedure includes application, initial verification, field survey, credit analysis, decision-making, contract signing, fund disbursement, and monitoring, which generally complies with operational standards. Obstacles encountered include incomplete documentation for prospective borrowers, limited human resources, lengthy survey processes, low financial literacy among the public, and late installment payments. Nevertheless, credit disbursement developments from 2021–2024 showed a positive trend with significant increases. This demonstrates that PT. BPR VII Koto continues to strive to improve service quality through administrative improvements, human resource capacity building, and the use of digital technology.